Juridical Analysis of Ecotourism Implementation in Gunung Kidul Regency - Edi Prianto; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
In line with development and economic growth, the role of tourism is increasing in various new sectors which are significant contributors of foreign exchange for increasing people's welfare. Indonesia as a country that has extraordinary natural and cultural wealth, also enjoys this benefit. However, tourism is also often considered as one of the biggest contributors to environmental and community sustainability, especially through the development of supporting infrastructure. Yogyakarta Province as a tourist destination, as well as environmental wisdom. Ecotourism, then seen as a tourist destination, can also be used as a solution to this problem. Using a qualitative approach, this study was conducted with the aim of formulating a sustainable ecotourism model based on cultural, social and environmental wisdom that will support the successful development of tourism in Yogyakarta. With the formulation of this policy model, it is hoped that in the future it will become a guideline for the government in developing national policies in the field of sustainable tourism in particular and supporting economic independence in the regions